2020
DOI: 10.1155/2020/7520924
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Treatment for Melanoma Brain Metastases

Abstract: Background. Historically, melanoma with brain metastases has a poor prognosis. In this retrospective medical record review, we report basic clinicopathological parameters and the outcomes of patients with melanoma and brain metastases treated with different treatment modalities before the era of immunotherapy and modern radiotherapy technique. Methods. Patients with metastatic melanoma were treated with surgery, radiotherapy, and/or systemic therapy from 1998 to 2017. In our study, they were identified and str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 43 publications
0
15
0
Order By: Relevance
“…Remarkably, feasibility of targeting intracranial melanoma upon systemic administration of MQ was demonstrated in a bioluminescent murine model, an important preclinical observation given the notoriously unsatisfactory clinical outcomes currently achieved using standard of care interventions in large patient populations afflicted by brain metastases (Figures 4 and 5). [10][11][12] Importantly, in the context of oral MQ targeting brain melanoma in a relevant murine model, it remains to be seen if MQ treatment may also impact molecular pathways involved in invasion and metastasis (such as regulation of epithelial-mesenchymal transition-related gene expression) blocking the occurrence of intracranial tumors, a topic of current research activities pursued in our laboratory. 34 Interestingly, molecular mechanisms of MQ-associated calcium dysregulation and ER-directed toxicity have been explored before in the context of MQ-induced neurotoxic symptoms observed in malaria patients, representing a well-documented adverse effect of this antimalarial intervention.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Remarkably, feasibility of targeting intracranial melanoma upon systemic administration of MQ was demonstrated in a bioluminescent murine model, an important preclinical observation given the notoriously unsatisfactory clinical outcomes currently achieved using standard of care interventions in large patient populations afflicted by brain metastases (Figures 4 and 5). [10][11][12] Importantly, in the context of oral MQ targeting brain melanoma in a relevant murine model, it remains to be seen if MQ treatment may also impact molecular pathways involved in invasion and metastasis (such as regulation of epithelial-mesenchymal transition-related gene expression) blocking the occurrence of intracranial tumors, a topic of current research activities pursued in our laboratory. 34 Interestingly, molecular mechanisms of MQ-associated calcium dysregulation and ER-directed toxicity have been explored before in the context of MQ-induced neurotoxic symptoms observed in malaria patients, representing a well-documented adverse effect of this antimalarial intervention.…”
Section: Discussionmentioning
confidence: 99%
“…3,9 In addition to BRAFi-resistance compromising clinical outcomes in melanoma patients, an urgent need exists for the identification of molecular therapeutics that can target these drug-resistant cells at metastatic sites including the brain. [10][11][12] Indeed, brain metastases are a frequent complication in patients with metastatic melanoma. Up to 45% of patients develop clinically documented brain tumors during their lifetime, and it has been reported that brain lesions are observable in more than 70% of melanoma patients at autopsy.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The treatment of brain metastatic lesions is further made challenging by the generally poor permeability of the blood-brain barrier to modern chemotherapeutics [ 44 ]. Surgery is the most effective method for patients with solitary CNS metastases [ 45 ].The National Comprehensive Cancer Network (NCCN) guideline recommended that surgical resection followed by whole brain radiation therapy (WBRT) or stereotactic radiation therapy (SRS) plus WBRT was appropriate for patients who had stable systemic disease or were newly diagnosed, while WBRT or SRS was advisable for patients who had multiple (>3) metastatic lesions [ 46 ]. Therefore, knowledge of the patterns of distant metastasis is crucial to personalize the treatment and follow-up strategies.…”
Section: Discussionmentioning
confidence: 99%